The Practice and Future of Financing Science, Technology, and Innovation - Ricardo Seidl da Fonseca (Foresight and STI Governance)
The importance of financing science, technology and innovation (STI) is growing increasingly relevant and is changing its content. New, more comprehensive financing mechanisms are emerging. With STI costs rising and government budgets shrinking, research and innovation has become more cooperative and network-based.